Civic Responsibility and Household Waste Segregation Practices: Basis For a Local Environmental Policy Framework - Maria Luisa S. Calanza; Randy D. Punzalan (Edukhasi: Jurnal Inovasi Pendidikan, 2026)
This study examines the relationship between civic responsibility and household waste segregation practices in developing a localized environmental policy framework grounded in behavioral evidence. While environmental awareness and civic engagement are widely recognized determinants of pro-environmental behavior, limited research has integrated these constructs within a combined behavioral and socio-ecological framework at the household level, particularly in Philippine barangay contexts. Guided by the Theory of Planned Behavior, Value-Belief-Norm Theory, and the Social-Ecological Model, a quantitative descriptive–comparative design was employed involving 385 household respondents in Cabuyao City, Laguna. Data were analyzed using descriptive statistics and one-way ANOVA at a 0.05 level of significance. Findings reveal a persistent intention–behavior gap, where high civic responsibility does not consistently translate into effective household waste segregation practices. Results indicate that structural and socio-economic factors, particularly educational attainment and household economic status, are stronger determinants of actual behavior than civic awareness alone. Although environmental knowledge and values are evident, they are insufficient to ensure sustained behavioral execution. The study demonstrates that household waste segregation behavior is more strongly shaped by structural constraints than cognitive or attitudinal factors, extending behavioral theory by emphasizing the critical role of perceived behavioral control in barangay settings. The study concludes that effective environmental governance requires strengthening institutional systems and household-level enabling conditions to improve consistent waste segregation practices.